2006
DOI: 10.1038/sj.bjc.6603038
|View full text |Cite
|
Sign up to set email alerts
|

Parallel cyclin E and cyclin A expression in neoplastic lesions of the uterine cervix

Abstract: Cyclin E levels are high during late G1 and early S-phase in normal cells. The cyclin E expression over the cell cycle in tumours is not fully known. The impact on patient outcome by high cyclin E levels during other parts of the cell cycle than late G1-and early S-phase is unknown. We set out to study the expression of cyclin E over the cell cycle in cervical carcinomas. Using immunofluorescence staining of cyclin A, digital microscopy, and digital image analysis, we determined which cells in a tissue section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…We also evaluated mouse reproductive tracts and their associated tumors for biomarkers commonly used for the diagnosis of human cervical cancers. Biomarkers included the E2F-responsive genes Mcm7, involved in DNA replication (20), and cyclin E, involved in the G 1 -S transition (21,22). We also monitored expression of the cyclin kinase inhibitor, p16.…”
Section: /K14e7mentioning
confidence: 99%
“…We also evaluated mouse reproductive tracts and their associated tumors for biomarkers commonly used for the diagnosis of human cervical cancers. Biomarkers included the E2F-responsive genes Mcm7, involved in DNA replication (20), and cyclin E, involved in the G 1 -S transition (21,22). We also monitored expression of the cyclin kinase inhibitor, p16.…”
Section: /K14e7mentioning
confidence: 99%
“…[10] We encountered a significant relationship between LSILs and the expression of the cyclins A and E [Table 2]. …”
Section: Discussionmentioning
confidence: 99%
“…[9] It has been reported that cyclin-E and cyclin-A expression is an indicator for poor outcome in cervical carcinomas associated with HR-HPV. [10]…”
Section: Introductionmentioning
confidence: 99%
“…This could be explained by its complex up-regulation by both E7 and E6 oncoproteins, making cyclin A active in both S phase and late G2 phase of the cell cycle. Cyclin A1 might be a useful marker of cell proliferation most notably orchestrated by the capability of E7 to abrogate the inhibitory activity of p21CIP1/WAF1/SDI1 on CDK and proliferating cell nuclear antigendependent DNA replication necessary for the G1-S transition (Erlandsson, F. et al, 2006). Studies on cyclin A as prognostic marker are limited.…”
Section: Cell Cycle Regulation Markersmentioning
confidence: 99%